Perceptions and landscape values in the English Lake District : a case study of Troutbeck Valley - Szász, Edina (SLU/Dept. of Biosystems and Technology (from 130101), 2017)
This thesis seeks to explore residents’ and visitors’ sense of place, in the form of a case study in the English Lake District National Park, which is under environmental, social, and economic pressures. It addresses the issue of local land use changes from an agroecological perspective and an attempt is being made to use the knowledge of landscape values and meanings for enhancing and sustaining the upland landscape. The main methods used are literature study, observations, and interviews, for which 14 residents and 14 visitors as key respondents were chosen. Analysis of the interview results involved the organization and thematic categorization of data. One relevant finding was the uniformity of the identified key categories and sub-categories for the sense of place constructed by the respondents, which was found primarily ‘recreational’ by visitors and predominantly ‘reassuring-comforting’ by residents. Physical and spatial components of the landscape were found to have a central role in constructing meanings. Iconic and aesthetic roles of sheep were highly valued, suggesting that historical past can contribute to the creation of landscape meanings, whereas gained products from sheep received much less attention. This finding was unexpected and may suggest a certain level of weakness in promoting local farm products. The results, furthermore, seem to support the idea that humans have an overall tendency to prefer diversity and to seek harmony between landscape elements. This may be extended to the heterogenous mosaic of agricultural and semi-natural components in the upland landscape with a desirable degree of diversity. On the one hand, the physical form of the landscape is considered to be the main contributor to the sense of wilderness. On the other hand, manmade elements of the landscape, however less attractive for the eyes, could convey the sense of ‘ordered wilderness’. Changes happen at a very slow scale in Troutbeck and this is one of the main reasons for finding the area attractive. Desired landscape would require the place to become preserved in present state in terms of its relative contentedness and tranquillity. Enhancement of the landscape may involve diversity and balance in the number of tourists, level of development, and rejuvenation of the village itself. This case study confirms that landscapes encompass more than just physical entity and it raises the question of what sort of landscape is desirable in the long term. Ancient values may be rethought and a deeper understanding of the right balance between natural and cultural must be prioritized. Whether to what extent it is possible to define balance, regarding the many different forms of opinions, this is a question that must be fully considered. One difficulty may be to reach an agreement as to where to set limits. An integrated view on nature and human beings may help this process. By recognizing various interpretations of potential users and key values, more access may be gained to ‘hidden aspects’ of the landscape (Arnesen, 2008) which contributes to a collective way of designing and the enrichment of places. The challenge is now to raise public awareness of landscape values, wider recognition of ecosystem services, and to develop appropriate pasture management regimes so as to support diversity. There is, therefore, definite need for communication and for a greater effort to reconnect producers to consumers. Future landscape changes are inevitable at the social, natural, and economic levels and investigating associations of these dimensions in future studies is recommended.